An empirical study on the development of socio-industrial adaptation of vocational education in China: A case of Southwest China - Xia, Zaiming; Wang, Hsuan-Po (Frontiers in Education, 2022)
With the rising strain of job rivalry in the contemporary social climate, the incapacity of recent graduates to adjust to society has become a pressing issue. College vocational education's social industry adaptability and students' job development skills are profoundly influenced by the growth direction of colleges, universities, and majors. Accordingly, 616 students and 11 instructors from three institutions in Southwest China serve as the research subjects for this study. The objective is to examine the societal support for colleges and universities in Southwest China, as well as the adaptation of colleges and universities to society, and to establish their link. and attempt to prove its psychological capital significance. Moreover, via the investigation of the interview questionnaires of instructors, we can learn the true requirements of students to adjust to social vocations. The findings indicate that (1) social support for colleges and universities may predict social adaption considerably and favorably. (2) Psychological capital has an important beneficial function as an intermediate between societal support for colleges and universities and the adaptation of institutions to society. (3) More attention and resources should be devoted to career preparation for students. Schools, as the primary institution, should build a variety of relationships with social businesses, and the steps taken to facilitate students' integration into society will assist schools in establishing their reputation. This contributes to the enhancement of the school's capacity for comprehensive management, so promoting the school's and society's virtuous growth cycle.